Super-hydrophobic self-repairing composite film for deicing fan blade and preparation method of super-hydrophobic self-repairing composite film
By applying a superhydrophobic self-healing composite membrane on the blades of the wind turbine, the superhydrophobic characteristics, self-healing function and aerodynamic response mechanism are integrated, and the contradiction between mechanical stability and surface functionality is solved, achieving a long-term anti-icing/de-icing effect in extreme environments.
Patent Information
- Application Number
- CN202510269055.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-07
- Publication Date
- 2025-06-03
AI Technical Summary
The prior art has failed to effectively solve the contradiction between mechanical stability and surface functionality in solving the problem of anti-icing of wind turbine blades. The single triggering mechanism makes the coating insufficient adaptability under different environmental conditions, making it difficult to achieve efficient and long-term anti-icing and de-icing effects.
A superhydrophobic self-healing composite membrane is adopted to achieve long-term anti-icing/de-icing by integrating superhydrophobic characteristics, self-healing functions and aerodynamic response mechanism. The composite film consists of a base layer, a functional layer and a superhydrophobic layer. The base layer is composited with isocyanate-based polyurethane and shape memory polymer. The functional layer introduces microcapsule materials and modified nano SiO2 particles. The superhydrophobic layer forms a micro-nano rough structure through electrospraying.
It realizes long-term anti-icing/de-icing in extreme environments. The self-healing function can cope with mechanical wear and environmental erosion. The shape memory polymer synergizes the ice layer by temperature-triggered deformation. The nanostructure enhances wear resistance and chemical inertia, and adapts to extreme environments such as low temperature and high humidity.
Smart Images

Figure BDA0005302122140000141 
Figure BDA0005302122140000151 
Figure BDA0005302122140000152
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of functional materials, and particularly relates to a superhydrophobic self-healing composite film for deicing fan blades and a preparation method thereof, which is particularly suitable for dynamic anti-icing / deicing of wind turbine blades under extreme climate conditions. Background Art
[0002] Under the general trend of global new energy development, wind power generation, as a clean and sustainable energy acquisition method, is widely used. Wind turbine blades are the key to capturing wind energy, and their performance directly affects power generation efficiency and stability. However, in cold regions or low-temperature environments such as high altitudes, the blade surface is extremely prone to icing, bringing many serious problems to wind power generation.
[0003] In the prior art, various measures have been taken for anti-icing and deicing of wind turbine blades, but there are certain limitations. First, the electrothermal deicing coating generates heat through electrothermal elements to melt ice. It is difficult to supply power and the stability is poor in remote wind farms, and the power supply cannot be guaranteed. In order to achieve an effective deicing effect, the coating thickness usually exceeds 500 μm. Such a thick coating will significantly increase the weight of the blade, change the aerodynamic shape of the blade, resulting in an increase in wind resistance, and thus reduce the wind energy capture efficiency and affect the power generation performance. More seriously, during the long-term operation of the blade, due to the influence of complex mechanical stress, temperature changes, and environmental erosion and other factors, microcracks are extremely likely to occur on the coating surface. And the coating itself lacks self-healing ability. Once microcracks appear, they will continue to accumulate and expand, and ultimately may lead to coating failure, greatly shortening the service life of the blade. Secondly, the microcapsule self-healing coating solves the self-healing problem by the rupture of microcapsules to release the repair agent, but the single thermal trigger release mechanism has a sharp reduction in efficiency to less than 40% at low temperatures, and the blade operation vibration will also damage the microcapsule distribution and weaken its self-healing function. Finally, the superhydrophobic anti-icing surface uses nanostructures to make the coating superhydrophobic to reduce ice adhesion. When the ice layer peels off, the nanostructures are prone to brittle fracture, and the contact angle drops significantly after 10 freeze-thaw cycles, the superhydrophobic performance deteriorates, and the anti-icing effect is reduced. Moreover, such surfaces lack dynamic response ability and cannot adjust the anti-icing strategy in a timely manner according to changes in actual environmental conditions (such as temperature, humidity, wind speed, etc.), and it is difficult to meet the anti-icing requirements of wind turbine blades in complex and changeable operating environments.
[0004] In the prior art, in solving the problem of anti-icing and deicing of wind turbine blades, the contradiction between mechanical stability and surface functionality has not been effectively solved. At the same time, the single trigger mechanism makes the coating insufficient in adaptability under different environmental conditions, and the coating system lacks synergistic optimization with the aerodynamic characteristics of the blade, resulting in the fact that the prior art is difficult to achieve efficient and long-term anti-icing and deicing effects in practical applications, and there is an urgent need to develop a new coating system to overcome these defects. Summary of the Invention
[0005] Aiming at the technical problems existing in the prior art, the present invention provides a superhydrophobic self-healing composite film for deicing of wind turbine blades and a preparation method thereof. By integrating superhydrophobic properties, self-healing functions and pneumatic response mechanisms, the film realizes the technical problems of long-term anti-icing / deicing in extreme environments.
[0006] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0007] A preparation method of a superhydrophobic composite film for deicing of wind turbine blades, comprising the following steps:
[0008] Dissolve isocyanate-based polyurethane and hydroxyl-containing shape memory polymer in cyclohexanone to obtain a mixed solution;
[0009] Spin-coat the mixed solution on the surface of glass fiber reinforced resin and cure it to form a base layer;
[0010] Mix the microcapsule material with a polyurea-poly(dopamine) hybrid shell and vinyl epoxy resin uniformly in methyl ethyl ketone, and then spin-coat it on the base layer and cure it to form a functional layer;
[0011] Spray the modified nano-SiO 2 particle suspension onto the functional layer to obtain a superhydrophobic layer, thereby forming a superhydrophobic self-healing composite film for deicing of wind turbine blades.
[0012] Furthermore, the modified nano-SiO 2 particle suspension is sprayed onto the functional layer by electrospray plating method;
[0013] The mass ratio of isocyanate-based polyurethane to hydroxyl-containing shape memory polymer is 10-20:3-5; the mass ratio of the microcapsule material with a polyurea-poly(dopamine) hybrid shell, vinyl epoxy resin and the modified nano-SiO 2 particle suspension is 3-5:10-15:15-20;
[0014] The surface of the glass fiber reinforced resin is treated through the following process: laser-etch the glass fiber reinforced resin to form roughness, wash it, soak it in an alkaline solution, and then wash it.
[0015] Furthermore, the microcapsule material with a polyurea-poly(dopamine) hybrid shell is prepared through the following process: dissolve fluorinated methacrylate monomers, photoinitiator, perfluoropolyether and diisocyanate monomers in an organic solvent to form an oil phase;
[0016] Add dopamine hydrochloride to water and adjust the pH to 8.0-9.0 to form an aqueous phase;
[0017] The oil phase is added to the water phase, and after ultrasonic emulsification, the reaction is carried out at 60-70 °C for 8-12 h to obtain microcapsule materials with a polyurea-polydopamine hybrid shell layer.
[0018] Further, the fluorinated methacrylate monomer is one or more of trifluoroethyl methacrylate, hexafluoroisopropyl methacrylate, dodecafluoroheptyl methacrylate, tridecafluorooctyl methacrylate, and perfluorocyclohexyl methyl acrylate.
[0019] Further, the photoinitiator is one or a mixture of two or more of the following components: 2,4,6-trimethylbenzoyl diphenylphosphine oxide, Irgacure 369, and Irgacure 819.
[0020] Further, the diisocyanate monomer is one or more of isophorone diisocyanate, dicyclohexylmethane diisocyanate, and diphenylmethane diisocyanate;
[0021] The organic solvent is xylene.
[0022] Further, the mass ratio of the fluorinated methacrylate monomer, photoinitiator, perfluoropolyether, diisocyanate monomer, and dopamine hydrochloride is 6-10 parts: 0.1-0.5: 2-5: 10-20.
[0023] Further, the modified nano-SiO 2 The particle suspension is prepared by the following process: The nano-SiO 2 is dispersed in anhydrous ethanol, ultrasonicated, filtered, and dried to obtain activated nano-SiO 2 ;
[0024] Vinyltriethoxysilane is mixed with an ethanol / water mixture, the pH is adjusted to 3.9-5.2, and the mixture is stirred and hydrolyzed for 1-2 h to obtain a hydrolyzate; the mass ratio of vinyltriethoxysilane to the ethanol / water mixture is 5-10:50-100;
[0025] The volume ratio of ethanol to water is 9:1;
[0026] The activated nano-SiO 2 is added to the hydrolyzate, and the reaction is carried out at 60-70 °C for 6-8 h under nitrogen protection, followed by centrifugation and drying to obtain double-bond functionalized nano-SiO 2 particles;
[0027] The double-bond functionalized nano-SiO 2 particles and methyl ethyl ketone are added to butyl acetate, and high-speed shear dispersion is carried out to obtain a suspension of modified nano-SiO 2 particles.
[0028] Further, the nano-SiO2 The particle size is 50 to 100 nm;
[0029] Double bond-functionalized nano-SiO 2 The mass ratio of the particles, methyl ethyl ketone and butyl acetate is 10 to 15:5 to 10:40 to 50.
[0030] A superhydrophobic composite film for deicing of fan blades.
[0031] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0032] In the present invention, when the surface of the microcapsule is damaged, the fluorine-containing substance is released to repair the hydrophobic layer. The shape memory polymer triggers deformation under temperature change, and combines with the pneumatic response to actively peel off the ice layer, realizing dynamic anti-icing / deicing. In the present invention, the microcapsule technology endows the material with self-repairing function, effectively coping with the decline of hydrophobic performance caused by mechanical wear or environmental erosion, and extending the service life. Modified nano-SiO 2 Particles enhance surface roughness and wear resistance, ensuring the stability of superhydrophobic performance in extreme environments. In extreme environments, the composite film may be damaged by factors such as sand, wind and ultraviolet rays. At this time, the microcapsule material plays a role and releases the repair component fluorinated methacrylate. In the present invention, the base layer is composed of a composite of polyurethane and a hydrophobic shape memory polymer, which improves the adhesion to the glass fiber reinforced resin and avoids delamination; the functional layer is formed by the composite curing of microcapsules and epoxy resin, forming a dense and flexible intermediate layer, further improving the mechanical strength and environmental adaptability of the overall structure. Through the synergistic effect of the superhydrophobic layer, the self-repairing microcapsules and the pneumatic response mechanism, the present invention significantly reduces the ice layer adhesion.
[0033] Furthermore, due to the good wetting performance of perfluoropolyether in the present invention, the fluorinated methacrylate can be diffused to the rupture point of the composite film. Under the action of a photoinitiator, the nano-SiO with double bonds 2 , fluorinated methacrylate and epoxy resin with double bonds can react to form chemical bonds, restoring the performance of the composite film and extending its service life and anti-icing effect.
[0034] Furthermore, the glass fiber reinforced resin substrate is treated by etching, ultrasonic cleaning, soaking in sodium hydroxide solution, etc. These treatments can remove impurities and oil stains on the substrate surface, increase the surface roughness of the substrate, form hydroxyl groups on the glass fiber surface, and the isocyanate groups of the isocyanate-based polyurethane polymer can react with the hydroxyl groups on the glass fiber surface and the shape memory polymer containing hydroxyl groups. The epoxy resin of the functional layer also contains rich epoxy groups and can also react with the isocyanate groups. After curing, the composite film can be firmly attached to the surface of the fan blade and is not easy to fall off.
[0035] Furthermore, the introduction of fluorinated monomers and perfluoropolyethers significantly enhances the chemical inertness of the composite membrane, which has excellent low-temperature resistance, ultraviolet resistance, and corrosion resistance, and is suitable for protecting wind turbine blades under harsh climate conditions such as high humidity, low temperature, or salt spray.
[0036] Furthermore, processes such as photoinitiated polymerization, ultrasonic emulsification, and electrospray plating are used to achieve uniform microcapsule sizes and uniform dispersion of nanoparticles, and avoid high-temperature and high-energy-consuming steps. Environmentally friendly solvents (such as xylene and methyl ethyl ketone) and low-toxicity monomers are preferably used to reduce the environmental burden during the production process. Detailed implementation manners
[0037] In order to make the technical problems, technical solutions, and beneficial effects solved by the present invention clearer, the following specific embodiments are used to further elaborate on the present invention in detail. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0038] Aiming at the problems of existing anti-icing technologies such as thick coatings, low self-healing efficiency, and easy brittle cracking of superhydrophobic surfaces, an efficient dynamic anti-icing solution is proposed by integrating a superhydrophobic layer, self-healing microcapsules, and a pneumatic response mechanism. The composite membrane is composed of a base layer, a functional layer, and a superhydrophobic layer: the base layer is made of isocyanate-based polyurethane and hydroxyl-containing shape memory polymer composites to enhance the adhesion to the blade substrate; the functional layer introduces polyurea-polydopamine hybrid shell microcapsules, which can release fluorine-containing substances to repair the hydrophobic surface when damaged; the superhydrophobic layer constructs a micro-nano rough structure through electrospray plating modified nano-SiO 2 suspension and improves hydrophobicity by combining perfluoropolyethers. The composite membrane has long-term anti-icing performance. Its self-healing function can cope with mechanical wear and environmental erosion. The shape memory polymer triggers deformation through temperature to cooperate with pneumatic ice peeling. At the same time, the nano-structure enhances wear resistance and chemical inertness, adapting to extreme environments such as low temperature and high humidity. The process of the present invention is green and efficient, and the raw materials are easily available, significantly reducing the operation and maintenance costs, providing intelligent and sustainable anti-icing protection for wind turbine blades.
[0039] The pneumatic response mechanism is an active de-icing method achieved by dynamically coupling the surface micro-structure design with the airflow during the operation of the blade. Its core lies in using the aerodynamic load generated by the rotation of the wind turbine blade, combined with the special micro-nano structure of the coating, to induce a controllable mechanical effect on the airflow, thereby actively weakening or peeling off the ice layer. The glass transition temperature T g of shape memory polyurethane SMPs is -10°C to 5°C (matching the icing temperature range). When the temperature drops to T < Tg, SMPs change from the rubber state to the glass state, and the depth of the surface micro-deep grooves spontaneously shrinks by 10 - 15%, squeezing the ice layer to generate micro-cracks. When the temperature rises to T > Tg, SMPs return to their original state, and the groove depth is restored, further expanding the ice layer cracks.
[0040] In the present invention, all parts are calculated by mass parts.
[0041] A preparation method of a superhydrophobic self-healing composite film for deicing of fan blades provided by the present invention comprises the following steps:
[0042] 1) Preparation of microcapsules: First, 6-10 parts by mass of fluorinated methacrylate monomers, 0.1-0.5 parts of photoinitiator, 2-5 parts of perfluoropolyether and 10-20 parts of diisocyanate monomers are dissolved in 50-100 parts of organic solvent to form an oil phase; Then, 3-6 parts of dopamine hydrochloride are added to 100-200 parts of deionized water, and a 2-4% (mass fraction) trihydroxymethylaminomethane buffer solution is slowly added to adjust the pH of the aqueous phase to 8.0-9.0 to form an aqueous phase. Finally, the oil phase is slowly added to the aqueous phase, the addition rate is controlled at 3 parts / min, ultrasonic emulsification and dispersion are carried out at 500 W for 0.5-1 h, and the reaction is carried out at 60-70 °C for 8-12 h to obtain microcapsule materials with a polyurea-polydopamine hybrid shell.
[0043] Among them, the fluorinated methacrylate monomers are one or more of trifluoroethyl methacrylate, hexafluoroisopropyl methacrylate, dodecafluoroheptyl methacrylate, tridecafluorooctyl methacrylate and perfluorocyclohexylmethyl acrylate.
[0044] The photoinitiator is one or a mixture of two or more of the following components: 2,4,6-trimethylbenzoyl diphenylphosphine oxide, Irgacure 369 and Irgacure 819.
[0045] The diisocyanate monomers are one or more of isophorone diisocyanate, dicyclohexylmethane diisocyanate and diphenylmethane diisocyanate.
[0046] The organic solvent is xylene;
[0047] 2) Preparation of modified nano-SiO 2 Particle suspension: First, 10-15 parts by mass of nano-SiO 2 is dispersed in 200-300 parts of absolute ethanol, ultrasonic treatment is carried out at 300 W for 30 min-60 min, filtered, and vacuum dried at 80 °C for 2 h to obtain activated nano-SiO 2 ; 5-10 parts of vinyltriethoxysilane and 50-100 parts of ethanol / water mixture (volume ratio of ethanol to water is 9:1) are mixed, the pH is adjusted to 3.9-5.2 with acetic acid, and stirred and hydrolyzed for 1-2 h to obtain a hydrolysis solution; The activated nano-SiO 2Add it to the hydrolysis solution, heat it to 60 - 70 °C under nitrogen protection, stir magnetically for 6 - 8 h, centrifuge at 500 - 1000 rpm / min, wash the solid with ethanol and acetone three times each, and dry it in vacuum at 60 °C for 12 - 24 h to obtain double-bond functionalized nano-SiO 2 particles. Add 10 - 15 parts of double-bond functionalized nano-SiO 2 particles and 5 - 10 parts of methyl ethyl ketone to 40 - 50 parts of butyl acetate, and disperse them by high-speed shearing to obtain a suspension of modified nano-SiO 2 particles.
[0048] Among them, the particle size of nano-SiO 2 is 50 - 100 nm.
[0049] 3) Preparation of the composite film: Dissolve 10 - 20 parts of isocyanate-based polyurethane (Dow VORASTAR HB 6700 isocyanate prepolymer) and 3 - 5 parts of hydroxyl-containing shape memory polymer (SMPs, thermosetting polyurethane shape memory polymer MP4510 produced by SMP Technologies Inc) in 50 - 60 parts of cyclohexanone to obtain a mixed solution. Then spin-coat the mixed solution evenly on the surface of a smooth and clean glass fiber-reinforced resin, and cure it at 80 °C for 2 h to form a base layer. Mix 3 - 5 parts of the microcapsule material with a polyurea-poly dopamine hybrid shell and 10 - 15 parts of vinyl epoxy resin (Dow Derakane411) evenly in 50 parts of methyl ethyl ketone, then spin-coat it on the base layer, remove bubbles in vacuum, and cure it at 60 °C for 1 h to form a functional layer. Using the electrospray plating method, with a voltage of 20 kV, a deposition rate of 0.1 - 0.3 mm / min, and a deposition time of 1 - 2 min, spray 15 - 20 parts of the suspension of modified nano-SiO 2 particles onto the functional layer to obtain a superhydrophobic layer, thereby forming a superhydrophobic self-healing composite film for deicing of fan blades.
[0050] Among them, the smooth and clean glass fiber-reinforced resin is prepared through the following process: Use laser etching to form roughness on the glass fiber-reinforced resin, perform ultrasonic cleaning for 0.5 - 1 h, soak it in a 0.5% sodium hydroxide solution by mass for 1 h, and wash it clean with ultrapure water.
[0051] The core principle of the present invention is to integrate superhydrophobic performance, self-healing function, and dynamic response mechanism through material innovation and multi-layer structure design to achieve long-term anti-icing / deicing of fan blades in extreme environments. The principle is as follows:
[0052] The superhydrophobic layer is composed of modified nano-SiO 2Particles form micro-nano rough structures through electrospray plating. Combining with the chemical inertness of perfluoropolyether, the contact angle of the composite film surface increases significantly, making it difficult for water droplets to wet and causing them to roll off quickly, greatly reducing the probability of ice nucleation. The introduction of perfluoropolyether further reduces the surface energy and enhances the hydrophobic stability. The geometric characteristics of the micro-nano structure (SiO with a particle size of 50 - 100 nm) 2 ) delay the icing process through multiple scattering effects, and at the same time, the wear resistance of the nanoparticles ensures the durability of the hydrophobic performance.
[0053] The microcapsules embedded in the functional layer are wrapped with a polyurea-poly dopamine hybrid shell containing a fluorinated methacrylate monomer and a photoinitiator. When cracks occur on the surface due to mechanical wear or environmental erosion, the microcapsules rupture and release repair components. Under the action of the photoinitiator, the fluorinated monomer undergoes free radical polymerization with the double bonds on the surface of nano-SiO 2 and the active groups in the epoxy resin, quickly repairing the damaged area and restoring the hydrophobic performance. Perfluoropolyether acts as a diffusion medium to ensure the efficient migration of the repair agent to the damage point, realizing in-situ self-repair.
[0054] The hydroxyl-containing shape memory polymer in the base layer has a thermal response property. When the temperature drops below the freezing point, the polymer chain segments undergo contraction deformation, resulting in micron-scale wrinkles on the surface of the composite film; when the temperature rises, the chain segments stretch and the surface returns to smoothness. This periodic deformation can mechanically break the adhesion interface between the ice layer and the film surface. Combining with the aerodynamic shear force (aerodynamic response mechanism) under the action of wind, the ice layer is actively peeled off, reducing energy dependence.
[0055] Isocyanate-based polyurethane and the shape memory polymer form a dense network through chemical cross-linking (the reaction between the isocyanate group and the hydroxyl group), enhancing the adhesion to the glass fiber-reinforced resin substrate; laser etching pretreatment of the substrate surface increases the roughness and hydroxyl density, strengthening the interface bonding. Vinyl epoxy resin (Dow Derakane411 in the United States) and the microcapsules are co-cured to form a flexible intermediate layer, which has both mechanical strength and self-repair ability, buffering the impact of external stress on the superhydrophobic layer. Nano-SiO 2 is functionalized with vinyl silane double bonds and covalently bonded to the epoxy resin to avoid particle shedding and ensure structural stability. Fluorinated monomers (such as tridecafluorooctyl methacrylate) and perfluoropolyether endow the composite film with excellent chemical inertness, resistance to ultraviolet aging, salt spray corrosion and low temperature tolerance (below -40 °C). The poly dopamine hybrid shell in the functional layer enhances the antioxidant property of the microcapsules, adapting to extreme climates such as high humidity and strong wind and sand.
[0056] The ultrasonic emulsification method is used to control the uniformity of the microcapsule particle size (the shell thickness is controllable), and photoinitiator polymerization avoids high-temperature energy consumption; the electrospray plating technology accurately regulates the deposition density of nanoparticles to form a uniform superhydrophobic layer. Environmentally friendly solvents (such as cyclohexanone, methyl ethyl ketone) and low-toxic raw materials reduce production pollution, meeting the requirements of green manufacturing.
[0057] Through the synergistic effect of the triple mechanisms of static anti-icing on the superhydrophobic surface, dynamic maintenance of microcapsule self-repair, and active de-icing of shape memory polymers, the present invention breaks through the single protection mode of traditional technologies. The multi-layer structure design takes into account both mechanical properties and environmental adaptability, ultimately realizing long-term and intelligent anti-icing of wind turbine blades under extreme conditions, while reducing operation and maintenance costs and energy consumption.
[0058] Example 1
[0059] A preparation method of a superhydrophobic composite film for de-icing of wind turbine blades provided by an embodiment of the present invention includes the following steps:
[0060] 1. Preparation of microcapsules
[0061] Dissolve 6 parts of trifluoroethyl methacrylate, 0.1 part of 2,4,6-trimethylbenzoyl diphenylphosphine oxide, 2 parts of perfluoropolyether, and 10 parts of isophorone diisocyanate in 50 parts of xylene to form an oil phase. Add 3 parts of dopamine hydrochloride to 100 parts of deionized water, slowly add a 2% mass fraction of tris(hydroxymethyl)aminomethane buffer solution, and adjust the pH to 8.0 to form an aqueous phase. Add the oil phase to the aqueous phase at a rate of 3 parts / min, perform ultrasonic emulsification at 500 W for 0.5 h, and react at 60 °C for 8 h to obtain microcapsule materials.
[0062] 2. Preparation of modified nano-SiO 2 Particle suspension
[0063] Disperse 10 parts of nano-SiO with a particle size of 50 nm 2 in 200 parts of absolute ethanol, perform ultrasonic treatment at 300 W for 30 min, filter, and vacuum dry at 80 °C for 2 h to obtain activated nano-SiO 2 . Mix 5 parts of vinyltriethoxysilane with 50 parts of an ethanol / water mixture (volume ratio of ethanol to water is 9:1), adjust the pH to 3.9 with acetic acid, stir and hydrolyze for 1 h to obtain a hydrolysis solution. Add the activated nano-SiO 2 to the hydrolysis solution, react at 60 °C for 6 h under nitrogen protection, and after centrifugal separation at 500 rpm / min, wash the solid with ethanol and acetone three times each, and vacuum dry at 60 °C for 12 h to obtain double-bond functionalized nano-SiO 2 particles. Add 10 parts of double-bond functionalized nano-SiO 2 and 5 parts of methyl ethyl ketone to 40 parts of butyl acetate, and perform high-speed shear dispersion to obtain a suspension.
[0064] 3. Preparation of the composite film
[0065] Dissolve 10 parts of isocyanate-based polyurethane and 3 parts of hydroxyl-containing shape memory polymer in 50 parts of cyclohexanone, and spin-coat it on the surface of glass fiber-reinforced resin that has been laser-etched, ultrasonically cleaned for 0.5 h, and immersed in a 0.5% sodium hydroxide solution by mass fraction for 1 h. Cure at 80 °C for 2 h to form a base layer.
[0066] Mix 3 parts of microcapsule material and 10 parts of vinyl epoxy resin (Dow Derakane 411 in the United States) evenly in 50 parts of methyl ethyl ketone, then spin-coat it on the base layer. After degassing in vacuum, cure at 60 °C for 1 h to form a functional layer. Using the electrospray plating method, with a voltage of 20 kV, a deposition rate of 0.1 mm / min, and a deposition time of 2 min, spray 15 parts of the modified nano-SiO 2 particle suspension onto the functional layer to obtain a superhydrophobic layer, thereby forming a superhydrophobic self-healing composite film for deicing of fan blades.
[0067] Example 2
[0068] It is basically the same as Example 1, but in the preparation of the microcapsules, the oil phase components are adjusted to: 8 parts of hexafluoroisopropyl methacrylate, 0.3 parts of Irgacure 369, 3 parts of perfluoropolyether, and 15 parts of dicyclohexylmethane diisocyanate, and the remaining steps are the same.
[0069] Example 3
[0070] It is basically the same as Example 1, but the particle size of the nano-SiO 2 particles is adjusted to 100 nm, and the remaining steps are the same.
[0071] Example 4
[0072] A preparation method of a superhydrophobic composite film for deicing of fan blades provided by an embodiment of the present invention includes the following steps:
[0073] 1. Preparation of microcapsules
[0074] Dissolve 10 parts of dodecafluorooctyl methacrylate, 0.1 part of Irgacure 369, 2 parts of perfluoropolyether, and 10 parts of isophorone diisocyanate in 50 parts of xylene to form an oil phase. Add 4 parts of dopamine hydrochloride to 100 parts of deionized water, slowly add a 2% by mass fraction of tris(hydroxymethyl)aminomethane buffer solution, and adjust the pH to 8.0 to form an aqueous phase. Add the oil phase to the aqueous phase at a rate of 3 parts / min, perform ultrasonic emulsification at 500 W for 0.5 h, and react at 60 °C for 8 h to obtain the microcapsule material.
[0075] 2. Preparation of modified nano-SiO 2 particle suspension
[0076] Disperse 15 parts of nano-SiO 2Dispersed in 200 parts of absolute ethanol, ultrasonic treated at 300 W for 30 min, filtered and vacuum dried at 80 °C for 2 h to obtain activated nano-SiO 2 。5 parts of vinyltriethoxysilane were mixed with 50 parts of ethanol / water mixture (volume ratio of ethanol to water is 9:1), the pH was adjusted to 3.9 with acetic acid, and stirred for hydrolysis for 1 h to obtain a hydrolysis solution. Activated nano-SiO 2 was added to the hydrolysis solution, reacted at 60 °C for 18 h under nitrogen protection, and after centrifugal separation at 1000 rpm / min, the solid was washed with ethanol and acetone three times each, and vacuum dried at 60 °C for 12 h to obtain double bond-functionalized nano-SiO 2 particles. 15 parts of double bond-functionalized nano-SiO 2 and 8 parts of methyl ethyl ketone were added to 40 parts of butyl acetate, and dispersed by high-speed shearing to obtain a suspension.
[0077] 3. Preparation of the composite film
[0078] 10 parts of isocyanate-based polyurethane and 4 parts of hydroxyl-containing shape memory polymer were dissolved in 50 parts of cyclohexanone, and spin-coated on the surface of glass fiber reinforced resin that had been laser etched, ultrasonically cleaned for 0.5 h and immersed in 0.5% by mass sodium hydroxide solution for 1 h, and cured at 80 °C for 2 h to form a base layer.
[0079] 3 parts of microcapsule material and 10 parts of vinyl epoxy resin (Dow Derakane411 in the United States) were mixed evenly in 50 parts of methyl ethyl ketone, and then spin-coated on the base layer. After vacuum defoaming, it was cured at 60 °C for 1 h to form a functional layer. Using the electrospray plating method, with a voltage of 20 kV, a deposition rate of 0.1 mm / min, and a deposition time of 1 min, 10 parts of the modified nano-SiO 2 particle suspension was sprayed onto the functional layer to obtain a superhydrophobic layer, thereby forming a superhydrophobic self-healing composite film for de-icing of fan blades.
[0080] Example 5
[0081] A preparation method of a superhydrophobic composite film for de-icing of fan blades provided by an embodiment of the present invention includes the following steps:
[0082] 1. Preparation of microcapsules
[0083] Dissolve 7 parts of hexafluoroisopropyl methacrylate, 0.5 part of Irgacure819, 5 parts of perfluoropolyether and 20 parts of isophorone diisocyanate in 100 parts of xylene to form an oil phase. Add 5 parts of dopamine hydrochloride to 200 parts of deionized water, slowly add a 4% (mass fraction) tris(hydroxymethyl)aminomethane buffer solution, and adjust the pH to 8.0 to form an aqueous phase. Add the oil phase to the aqueous phase at a rate of 3 parts / min, perform ultrasonic emulsification at 500 W for 1 h, and react at 70 °C for 8 h to obtain the microcapsule material.
[0084] 2. Preparation of modified nano-SiO 2 Particle suspension
[0085] Disperse 12 parts of nano-SiO with a particle size of 70 nm 2 in 300 parts of absolute ethanol, perform ultrasonic treatment at 300 W for 30 min, filter, and then vacuum dry at 80 °C for 2 h to obtain activated nano-SiO 2 . Mix 7 parts of vinyltriethoxysilane with 100 parts of an ethanol / water mixture (volume ratio of ethanol to water is 9:1), adjust the pH to 5.2 with acetic acid, and stir and hydrolyze for 2 h to obtain a hydrolysis solution. Add the activated nano-SiO 2 to the hydrolysis solution, react at 66 °C for 7 h under nitrogen protection, after centrifugal separation at 700 rpm / min, wash the solid with ethanol and acetone 3 times each, and vacuum dry at 60 °C for 24 h to obtain double-bond functionalized nano-SiO 2 particles. Add 12 parts of double-bond functionalized nano-SiO 2 and 10 parts of methyl ethyl ketone to 50 parts of butyl acetate, and perform high-speed shear dispersion to obtain a suspension.
[0086] 3. Preparation of composite film
[0087] Dissolve 15 parts of isocyanate-based polyurethane and 5 parts of hydroxyl-containing shape memory polymer in 55 parts of cyclohexanone, spin-coat on the surface of a glass fiber-reinforced resin that has been laser-etched, ultrasonically cleaned for 0.5 h, and immersed in a 0.5% (mass fraction) sodium hydroxide solution for 1 h, and cure at 80 °C for 2 h to form a base layer.
[0088] Mix 4 parts of the microcapsule material and 15 parts of vinyl epoxy resin (Dow Derakane411 in the United States) evenly in 50 parts of methyl ethyl ketone, then spin-coat on the base layer, remove bubbles under vacuum, and cure at 60 °C for 1 h to form a functional layer. Using the electrospray plating method, with a voltage of 20 kV, a deposition rate of 0.3 mm / min, and a deposition time of 2 min, spray 15 parts of the modified nano-SiO 2 particle suspension onto the functional layer to obtain a superhydrophobic layer, thereby forming a superhydrophobic self-healing composite film for de-icing of fan blades.
[0089] Example 6
[0090] A preparation method of a superhydrophobic composite film for deicing of fan blades provided by an embodiment of the present invention includes the following steps:
[0091] 1. Preparation of microcapsules
[0092] Dissolve 9 parts of a mixture of tridecafluorooctyl methacrylate and perfluorocyclohexylmethyl acrylate (the molar ratio of tridecafluorooctyl methacrylate to perfluorocyclohexylmethyl acrylate is 1:1), 0.4 parts of a mixture of 2,4,6-trimethylbenzoyl diphenylphosphine oxide and Irgacure 819 (the molar ratio of 2,4,6-trimethylbenzoyl diphenylphosphine oxide to Irgacure 819 is 1:1), 4 parts of perfluoropolyether, and 17 parts of isophorone diisocyanate in 70 parts of xylene to form an oil phase. Add 6 parts of dopamine hydrochloride to 150 parts of deionized water, slowly add a 3% (by mass) tris(hydroxymethyl)aminomethane buffer solution, and adjust the pH to 9.0 to form an aqueous phase. Add the oil phase to the aqueous phase at a rate of 3 parts / min, perform ultrasonic emulsification at 500 W for 1 h, and react at 65 °C for 10 h to obtain microcapsule materials.
[0093] 2. Preparation of modified nano-SiO 2 Particle suspension
[0094] Disperse 10 parts of nano-SiO with a particle size of 80 nm 2 in 250 parts of absolute ethanol, perform ultrasonic treatment at 300 W for 30 min, filter, and vacuum dry at 80 °C for 2 h to obtain activated nano-SiO 2 . Mix 10 parts of vinyltriethoxysilane with 80 parts of an ethanol / water mixture (the volume ratio of ethanol to water is 9:1), adjust the pH to 4.5 with acetic acid, and stir and hydrolyze for 1.5 h to obtain a hydrolysis solution. Add the activated nano-SiO 2 to the hydrolysis solution, react at 70 °C for 6 h under nitrogen protection, perform centrifugal separation at 800 rpm / min, and wash the solid with ethanol and acetone three times each, and vacuum dry at 60 °C for 20 h to obtain double-bond functionalized nano-SiO 2 particles. Add 10 parts of double-bond functionalized nano-SiO 2 and 5 parts of methyl ethyl ketone to 55 parts of butyl acetate, and perform high-speed shear dispersion to obtain a suspension.
[0095] 3. Preparation of the composite film
[0096] Dissolve 20 parts of isocyanate-based polyurethane and 3 parts of a hydroxyl-containing shape memory polymer in 60 parts of cyclohexanone, spin-coat on the surface of a glass fiber-reinforced resin that has been laser-etched, ultrasonically cleaned for 0.5 h, and immersed in a 0.5% (by mass) sodium hydroxide solution for 1 h, and cure at 80 °C for 2 h to form a base layer.
[0097] After mixing 5 parts of microcapsule material and 12 parts of vinyl epoxy resin (Dow Derakane 411 in the United States) uniformly in 50 parts of methyl ethyl ketone, it was spin-coated on the base layer. After degassing under vacuum, it was cured at 60 °C for 1 h to form a functional layer. Using the electrospray plating method, with a voltage of 20 kV, a deposition rate of 0.2 mm / min, and a deposition time of 1 min, 20 parts of the modified nano-SiO 2 particle suspension was sprayed onto the functional layer to obtain a superhydrophobic layer, thereby forming a superhydrophobic self-healing composite film for deicing of fan blades.
[0098] Comparative Example 1
[0099] It was basically the same as Example 1, but the microcapsule material was not added, and the remaining steps were the same.
[0100] Comparative Example 2
[0101] It was basically the same as Example 1, but the surface treatment of the glass fiber reinforced resin was not carried out, and the remaining steps were the same.
[0102] Comparative Example 3
[0103] It was basically the same as Example 1, but the modified nano-SiO 2 particles were not added, and the remaining steps were the same.
[0104] The performance test methods and results of Examples 1-3 and Comparative Examples 1-3 are as follows:
[0105] 1. Static contact angle test
[0106] Using a contact angle measuring instrument, samples with a size of 2 cm × 2 cm were cut from the composite films prepared in the examples and comparative examples. The samples were fixed on the stage of the contact angle measuring instrument. 2 μL of deionized water was dropped onto the surface of the samples using a micro syringe. Static images of the water droplets on the sample surface were taken. The software was used to analyze the images, and the contact angle between the water droplets and the sample surface was calculated. The results are shown in Table 1.
[0107] Table 1 Static contact angle test results
[0108] Sample Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Contact Angle (°) 155±2 153±2 156±3 142±3 135±2 101±3
[0109] 2. Dynamic deicing performance test
[0110] A low-temperature wind tunnel experimental device is adopted, equipped with a temperature control system, a wind speed regulation system, and an ice adhesion tester. The composite films prepared in the examples and comparative examples are installed on the simulated fan blades. The simulated fan blades are placed in the low-temperature wind tunnel, with the temperature set at -10°C, the wind speed at 10 m / s, and the humidity at 90%. Cold air and water mist are introduced to form ice layers on the blade surface. Observe the formation of the ice layers, record the ice layer thickness and adhesion. Start the de-icing program, observe the shedding of the ice layers, and record the de-icing time. The results are shown in Table 2.
[0111] Table 2 Dynamic De-icing Performance Test Results
[0112]
[0113] 3. Abrasion Resistance Test
[0114] An abrasion resistance tester is used to cut out samples with a size of 5 cm × 5 cm from the composite films prepared in the examples and comparative examples. The samples are fixed on the stage of the abrasion resistance tester, and sandpaper with a particle size of 800 mesh is selected and installed on the grinding head of the tester. Set the rotation speed of the grinding head at 60 rpm and apply a pressure of 500 g. Perform 50 rotations and observe the wear condition of the sample surface. Use a contact angle measuring instrument to measure the contact angle of the worn sample surface. The results are shown in Table 3.
[0115] Table 3 Abrasion Resistance Test Results
[0116]
[0117] 4. Durability Test
[0118] A freeze-thaw cycle test chamber equipped with a temperature control system is used. Samples with a size of 5 cm × 5 cm are cut from the composite films prepared in the examples and comparative examples. The samples are placed in the freeze-thaw cycle test chamber, with the temperature set at -20°C and maintained for 2 hours. Then the temperature is raised to 25°C and maintained for 2 hours. Repeat the above steps for 10 freeze-thaw cycles. Use a contact angle measuring instrument to measure the contact angle of the sample surface after the freeze-thaw cycles. The results are shown in Table 4.
[0119] Table 4 Durability Test Results
[0120]
[0121] Through the above performance test methods, the performance of the composite films in the examples and comparative examples was evaluated. The test results show that the superhydrophobic composite film of the present invention exhibits significant advantages in terms of static contact angle, dynamic de-icing performance, abrasion resistance, and durability. The microcapsule material, modified nano-SiO 2The surface treatment of particles and glass fiber reinforced resin plays a key role in improving the performance of the composite film. The composite film of the present invention can effectively meet the anti-icing / de-icing requirements of wind turbine blades under extreme climatic conditions and has broad application prospects.
[0122] The above embodiments are only one of the implementation manners capable of implementing the technical solution of the present invention. The scope of protection required by the present invention is not limited only by this embodiment, but also includes any changes, substitutions and other implementation manners that are easily conceivable by those skilled in the art within the technical scope disclosed by the present invention.
Claims
1. A method for preparing a super-hydrophobic composite film for deicing fan blades, characterized in that: The steps include: dissolving isocyanate-based polyurethane and hydroxyl-containing shape memory polymer in cyclohexanone to obtain a mixed solution; Spin-coating the mixed solution on the surface of the glass fiber reinforced resin and curing it to form a base layer; The microcapsule material with a polyurea-polydopamine hybrid shell layer and a vinyl epoxy resin are mixed evenly in methyl ethyl ketone, and then spin-coated on the substrate layer and cured to form a functional layer; The modified nano-SiO2 particle suspension is sprayed onto the functional layer to obtain a super-hydrophobic layer, thereby forming a super-hydrophobic self-repairing composite film for deicing wind turbine blades.
2. The method for preparing a super-hydrophobic composite film for deicing fan blades according to claim 1, characterized in that: The modified nano-SiO2 particle suspension is sprayed onto the functional layer by electrospraying; The mass ratio of isocyanate-based polyurethane to hydroxyl-containing shape memory polymer is 10-20:3-5; the mass ratio of microcapsule material of polyurea-polydopamine hybrid shell layer, vinyl epoxy resin and modified nano-SiO2 particle suspension is 3-5:10-15:15-20; The surface of the glass fiber reinforced resin is processed by the following processes: the glass fiber reinforced resin is laser etched to form roughness, cleaned, immersed in an alkaline solution, and cleaned.
3. The method for preparing a super-hydrophobic composite film for deicing fan blades according to claim 1, characterized in that: The microcapsule material with a polyurea-polydopamine hybrid shell layer is prepared by the following process: dissolving a fluorinated methacrylate monomer, a photoinitiator, a perfluoropolyether and a diisocyanate monomer in an organic solvent to form an oil phase; Add dopamine hydrochloride to water to adjust the pH to 8.0-9.0 to form an aqueous phase; The oil phase is added to the water phase, and after ultrasonic emulsification, the reaction is carried out at 60-70° C. for 8-12 hours to obtain a microcapsule material with a polyurea-polydopamine hybrid shell layer.
4. The method for preparing a super-hydrophobic composite film for deicing fan blades according to claim 3, characterized in that: The fluorine-containing methacrylate monomer is one or more of trifluoroethyl methacrylate, hexafluoroisopropyl methacrylate, dodecafluoroheptyl methacrylate, tridecafluorooctyl methacrylate and perfluorocyclohexyl methyl acrylate.
5. The method for preparing a super-hydrophobic composite film for deicing fan blades according to claim 3, characterized in that: The photoinitiator is one or a mixture of two or more of the following components: 2,4,6-trimethylbenzoyldiphenylphosphine oxide, Irgacure369 and Irgacure819.
6. The method for preparing a super-hydrophobic composite film for deicing fan blades according to claim 3, characterized in that: The diisocyanate monomer is one or more of isophorone diisocyanate, dicyclohexylmethane diisocyanate and diphenylmethane diisocyanate; The organic solvent is xylene.
7. The method for preparing a super-hydrophobic composite film for deicing fan blades according to claim 3, characterized in that: The mass ratio of the fluorinated methyl acrylate monomer, the photoinitiator, the perfluoropolyether, the diisocyanate monomer and the dopamine hydrochloride is 6 to 10 parts: 0.1 to 0.5: 2 to 5: 10 to 20.
8. The method for preparing a super-hydrophobic composite film for deicing wind turbine blades according to claim 1, characterized in that: The modified nano-SiO2 particle suspension is prepared by the following process: dispersing the nano-SiO2 in anhydrous ethanol, ultrasonically treating, filtering, and drying to obtain activated nano-SiO2; Mixing vinyl triethoxysilane with an ethanol / water mixture, adjusting the pH to 3.9-5.2, stirring and hydrolyzing for 1-2 hours to obtain a hydrolyzate; the mass ratio of vinyl triethoxysilane to the ethanol / water mixture is 5-10:50-100; The volume ratio of ethanol to water is 9:1; Add the activated nano-SiO2 to the hydrolyzate, react at 60-70°C for 6-8h under nitrogen protection, centrifuge and dry to obtain double-bond functionalized nano-SiO2 particles; Double-bond functionalized nano-SiO2 particles and methyl ethyl ketone are added into butyl acetate and dispersed by high-speed shearing to obtain a modified nano-SiO2 particle suspension.
9. The method for preparing a super-hydrophobic composite film for deicing wind turbine blades according to claim 8, characterized in that: The particle size of nano-SiO2 is 50-100nm; The mass ratio of double-bond functionalized nano-SiO2 particles, methyl ethyl ketone and butyl acetate is 10-15:5-10:40-50.
10. A super-hydrophobic composite film for deicing wind turbine blades prepared according to the method according to any one of claims 1 to 9.
Citation Information
Cited By
Anti-icing and wave-transmitting integrated glass fiber composite material and preparation method thereof
CN122013536A